Multifunctional biological approaches for enhanced pesticide removal in agroecosystems: a path toward soil remediation - Cruz, Victor Hugo; Simionatto, Henzo Henrique; Ribeiro, Emanuella Roberto; Frias, Yanca Araujo; Valério, Thalia Silva; Lopes, Paulo Renato Matos (Frontiers in Agronomy, 2026)
The widespread and indiscriminate use of pesticides in modern agriculture has caused severe environmental contamination, significantly affecting terrestrial and aquatic ecosystems and non-target organisms. To meet this challenge, it is necessary to improve bioremediation techniques such as phytoremediation, bioaugmentation, biostimulation, and vermiremediation. The key findings highlight the synergistic potential of combining these approaches to accelerate pesticide degradation and improve remediation outcomes. Plant families such as Fabaceae and Poaceae have demonstrated significant ability for phytoremediation, with species such as Canavalia ensiformis and Zea mays excelling in the remediation of herbicides and insecticides. Microbial genera such as Bacillus, Pseudomonas, and Streptomyces play a key role as essential contributors to the degradation process, particularly when associated with plants. The integration of organic additives, such as vinasse, further improves the interactions between plants, microbes, and soil fauna, increasing the efficiency of remediation. In addition, the role of vermiremediation using earthworms such as Eisenia foetida to improve soil aeration and microbial activity has received attention. Therefore, approaches combining phytoremediation with bioaugmentation, biostimulation, and vermiremediation could offer a scalable and sustainable pathway to accelerate pollutant degradation, restore soil health, and promote agricultural sustainability. Future research should focus on the optimization of these techniques, the exploration of genetic advances to enhance microbial and plant remediation capabilities, and the assessment of their feasibility at a global scale. These efforts are vital for mitigating the environmental impacts of pesticides and for promoting a more resilient agricultural system.